Optic Disc Features in Familial Retinal Arteriolar Tortuosity - Sinner, Veronika; Heckmann, Jan; Sturm, Veit; Valmaggia, Christophe; Todorova, Margarita G. (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose Describing optic disc appearance in familial retinal arteriolar tortuosity (fRAT) using multimodal imaging and raising awareness of peripapillary arterial changes due to this disorder.Methods A cross-sectional study was performed in four consecutive patients of two non-related families. Detailed ophthalmological examination was performed and supported by medical and family history and multimodal imaging.Results In all subjects, increased tortuosity of second- and third-order retinal arteries in superior and deeper vascular plexus was documented. Furthermore, tortuosity in the peripapillary circle of Zinn-Haller was found. In addition, retinal vessel oximetry confirmed tortuosity only of the arterial vessels.Conclusion The present data suggests that a blurry bordered, hyperemic optic disc in the presence of abnormally tortuous arteriolar vessels and asymptomatically or oligosymptomatically spontaneously resolved hemorrhages could be associated with a fRAT. This finding could be linked to peripapillary arterial vessel tortuosity.
Keywords: familial retinal arteriolar tortuosity; hyperemic optic disc; arterial tortuosity; retinal hemorrhages